Using Werewolf Game to Improve Students’ Speaking Skill at the Second Grade of SMPN 33 Padang - Rima Angelina; Rahma Dania; Suparmi Suparmi (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2024)
The problem of this research is students’ low speaking skills; students are afraid, nervous, and less interested in learning English. The purpose of the study is to improve students' speaking skills using the Werewolf game. This research was conducted at SMP N 33 Padang. The researcher only took one class as a sample. The sample consisted of 31 students from class VIII 4 who were chosen using cluster random sampling. This study used a quantitative method with a pre-experimental approach. The experimental group was taught the Werewolf game. The data collection instrument was an oral test. The experimental group was given a pre-test and a post-test. The pre-test result showed the average experimental class score was 57.42 and the post-test was 66.06. After the data is collected, the data is analyzed using the t-test formula. The results of the analysis showed that the value of t test> t table is 3.695 > 2.0454. The last hypothesis shows that Ho is rejected and Ha is accepted. This means that there is a significant influence on improving students' speaking skills using the Werewolf game.